2021
DOI: 10.3390/pathogens10040448
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya and Zika Viruses: Co-Circulation and the Interplay between Viral Proteins and Host Factors

Abstract: Chikungunya and Zika viruses, both transmitted by mosquito vectors, have globally re-emerged over for the last 60 years and resulted in crucial social and economic concerns. Presently, there is no specific antiviral agent or vaccine against these debilitating viruses. Understanding viral–host interactions is needed to develop targeted therapeutics. However, there is presently limited information in this area. In this review, we start with the updated virology and replication cycle of each virus. Transmission b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 241 publications
0
4
0
Order By: Relevance
“…The occurrence of triterpenes, steroids, or polyphenols – classes of compounds previously reported to possess anti‐ZIKV activity, as discussed throughout the manuscript – was the chemosystematic criteria adopted for plant selection. Besides, we prioritized plants with reported anti‐inflammatory activity, since the antiviral effect of some natural products has been assigned to the anti‐inflammatory responses induced in the host cells [7,8] . Eight compounds and a mixture of triterpenes isolated from the tested plant species, or selected by the same approach, were also assayed for their anti‐ZIKV activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of triterpenes, steroids, or polyphenols – classes of compounds previously reported to possess anti‐ZIKV activity, as discussed throughout the manuscript – was the chemosystematic criteria adopted for plant selection. Besides, we prioritized plants with reported anti‐inflammatory activity, since the antiviral effect of some natural products has been assigned to the anti‐inflammatory responses induced in the host cells [7,8] . Eight compounds and a mixture of triterpenes isolated from the tested plant species, or selected by the same approach, were also assayed for their anti‐ZIKV activity.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, we prioritized plants with reported anti-inflammatory activity, since the antiviral effect of some natural products has been assigned to the anti-inflammatory responses induced in the host cells. [7,8] Eight compounds and a mixture of triterpenes isolated from the tested plant species, or selected by the same approach, were also assayed for their anti-ZIKV activity.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding Ae. aegypti , CHIKV could co-infect with other arboviruses known to be sympatric and co-circulating, such as YFV [ 111 ], ZIKV [ 112 , 113 ], or JEV [ 114 ]. The co-circulation of these flaviviruses with CHIKV in the same geographical area [ 115 ] has been highlighted by the co-infection of patients with ZIKV and CHIKV [ 116 ].…”
Section: Introductionmentioning
confidence: 99%
“…ZIKV possesses a positive single-stranded RNA that encodes a polyprotein precursor that is processed by cellular and viral proteases to yield the three structural proteins: the capsid (C), the precursor of membrane (prM), and the envelop (E), followed by seven nonstructural proteins: NS1 to NS5. The African and Asian ZIKV strains have been extensively studied (Wichit et al, 2021). Due to their genetic difference, it has been shown that the two ZIKV lineages differentially infect and lyse human placental trophoblast (Sheridan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%